Change in a product between 2 states as the symmetrical sum of changes in each of its factors - Geary, R.C; John, A.A. (Economic & Social Studies, 1983)
This paper is concerned with the algebraic problem of expressing the change in a product purely in terms of changes in its factors; denoting two states by 1 and 2 (indicated by superscripts) and defining variables X; (i = 1,2, . . . ,k).
Keywords: Mathematics; Algebra